Inflation and Stock Market Returns in Indonesia - Astriandina, Irsa (2006)
Indonesia is the fourth most populous country in the world. It has adopted a market-based economy in which the government plays a significant role. The country has more than 164 state-owned enterprises and administers prices on several basic goods including fuel and rice. Indonesia was also one of the Southeast Asian countries whose high performing and newly industrialized economy showed impressive growth from the early 1980s until the late 1990s when the financial crisis struck. The financial crisis in Asia was triggered by the devaluation of Thailands Baht in 1997. The Thai Baht suffered a significant devaluation after the currency was attacked by massive speculations and approximately two months after Finance One, the largest finance company in Thailand, went bankrupt (Garay, 2003). The devaluation of Thai Baht was soon followed by the devaluation of Indonesian Rupiah, Malaysian Ringgit and a few other Asian currencies.